Determinants of childhood immunizations in Senegal: Adding previous shots to sociodemographic background - Patrick Peretti-Watel; Sébastien Cortaredona; Elhadji Yaya Ly; Valérie Seror; Samba Ndiaye; Ibrahima Gaye; Mouhamadou Fall (Taylor & Francis Group, 2020)
Introduction. Today, in Sub-Saharan Africa, vaccine-preventable diseases still contribute heavily to high child mortality. Maintaining high coverage rates for childhood vaccines and reducing related social inequalities are public health priorities in Senegal. Our aim was to investigate the determinants of childhood vaccination, including sociodemographic factors and previous vaccine-related decision-making. Methods. Data come from the 2016 Senegalese Demographic and Health Survey, a nationally representative household survey targeting women aged 15-49, with a questionnaire focusing on health and reproductive issues, including their children's health. We restricted the analysis to children aged 12-23 months (n = 1,143). We used bivariate and multivariate analyses for investigating the determinants of several childhood vaccinations (Bacillus Calmette-Guérin, pentavalent, polio, measles and yellow fever vaccines), including sociodemographic factors and previous shots. Results. We identified two main sociodemographic predictors of childhood vaccination in Senegal: the mother's education level, which was strongly and positively correlated to every vaccination considered, except from the BCG vaccination, and the region of residence, with higher vaccination coverage rates in the Centre and West of Senegal. Moreover, previous shots were also strongly predictive of subsequent shots. Conclusion. The positive impact of mother's education on child vaccination illustrates the wide-ranging benefits of educating girls, while the regional variability of immunization rates requires more research to be better understood. Previous shots are probably a proxy variable for unobservable factors strongly correlated to vaccinations, but beyond this 'proxy effect', they may also have their own specific effect on following shots. We believe this topic deserves further research.